Pola Penanganan dan Aliran Materi Sampah B3 Rumah Tangga di Kabupaten Sleman (Sanitasi: Jurnal Kesehatan Lingkungan, 2015)
Household solid waste containing hazardous and toxic materials is still treated similarly withdomestic waste. Material flow of household hazardous solid waste (HHSW) follows the pattern ofwaste management in an area. Most of the waste (85,52 %) in Sleman district including HHSW isjust burned or dumped into the rivers, the yards and at illegal dumping sites, while the other11,85 % is transported and disposed into the final disposal site (TPA Piyungan) and approximately the 2,63 % of the waste is sorted, collected and sold by community-based solid waste management (CBSWM) groups. HHSW generation in Sleman district is 2,438 g/person/day or 2.81tons/day in 2013 and has the following characteristics: explosive, flammable, reactive, toxic, infectious and corrosive. Material flow of HHSW is influenced by the activities of the informal sector(scavengers and middleman) who picked up valuable types of HHSW (recycleable) and sell torecyclers (factories) thereby potentially reducing the impact of environmental pollution (air, water,soil). The community-based solid waste management system (independent pattern) can reducethe most amount of HHSW that is discharged into the environment, i.e. 85,41 %, meanwhile themunicipal solid waste service system (urban pattern) reduces 80,30 % and the rural waste management system (rural pattern) reduces 47,55 %